Implementation of HIV/AIDS Screening Services for Pregnant Women at the Sentani Health Center - Wiwit Vitania; Yustika Rahmawati Pratami; Hasnia Hasnia; Wise Raya Batoteng; Yefi Sofia Warmer; Vrin Welmince Asmuruf; Nawang Wulan Nago Pitasari (ARMADA : Jurnal Penelitian Multidisiplin, 2025)
HIV screening in pregnant women is an important step to prevent mother-to-child transmission of HIV and ensure proper treatment for infected mothers. This study aims to evaluate the implementation of HIV/AIDS screening services for pregnant women at the Sentani Health Center, Jayapura Regency, in 2024. This study used qualitative methods with a phenomenological approach. The number of participants in this study was 6 participants consisting of pregnant women, midwives and P2P officers who involved in-depth interviews. The results of the study showed that although the HIV screening program for pregnant women had been implemented according to the guidelines, there were several obstacles that affected the effectiveness of the implementation, such as limited officers, lack of knowledge of pregnant women about the importance of screening, and the stigma associated with HIV/AIDS. In addition, inadequate facilities and test kits are also challenges in providing optimal services. This study suggests the need for increased training for health workers, further socialization to the community, and improved facilities and equipment to support the implementation of more effective and efficient HIV/AIDS screening.